Chromogranin A levels in the cerebrospinal fluid of patients with amyotrophic lateral sclerosis - Verde, Federico; Steinacker, Petra; Oeckl, Patrick; Weishaupt, Jochen H.; Rosenbohm, Angela; Silani, Vincenzo; Ludolph, Albert C.; Otto, Markus (Neurobiology of aging, 2018)
Chromogranin A (CgA) is a protein found in large dense-core vesicles of neuroendocrine cells and neurons and regulating secretion. A relevance to amyotrophic lateral sclerosis (ALS) was suggested as its overexpression accelerates disease onset in model systems and it interacts with mutant forms of SOD1. Recently, increased cerebrospinal fluid (CSF) CgA levels have been reported in ALS patients relative to controls. With the aim of confirming this finding, we measured CgA and phosphorylated neurofilament heavy chain (pNFH), an established ALS biomarker, in the CSF of 32 ALS patients and 32 disease controls. ALS patients had clearly increased pNFH levels (p < 0.0001), while CgA levels were only modestly lower relative to controls (p = 0.0265), with wide value overlap and consequently poor discriminative performance. CgA did not correlate with any disease parameters among ALS patients. Our findings suggest that CgA is not a promising clinical biomarker for ALS.
Gesehen am 08.07.2021